2014
DOI: 10.3233/ifs-141121
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence based modeling and optimization of heat affected zone in Nd:YAG laser cutting of duralumin sheet

Abstract: Duralumin is an alloy of aluminium which has some unique properties such as high strength to weight ratio, high resistance to corrosion, light in weight, and more demanding alloy in various sectors such as space craft, marine, chemical industries, construction and automobile. These applications require very precise and complex shapes which may not be obtained with conventional machining. Pulsed Nd:YAG laser cutting may be used to fulfill these objectives by using optimum setting of process parameters. The pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Vagheesan et al [12] also applied a neural network and particle swarm optimization (PSO) based modelling and optimization approach for the study of laser cutting (CO2 laser) of aluminium alloys. Norkey et al [13] also attempted an ANN-based modelling technique for studying the HAZ for laser machining of aerospace material like duralumin.…”
Section: Introductionmentioning
confidence: 99%
“…Vagheesan et al [12] also applied a neural network and particle swarm optimization (PSO) based modelling and optimization approach for the study of laser cutting (CO2 laser) of aluminium alloys. Norkey et al [13] also attempted an ANN-based modelling technique for studying the HAZ for laser machining of aerospace material like duralumin.…”
Section: Introductionmentioning
confidence: 99%
“…NNs are capable of predicting ideal parameter settings by effectively modelling intricate and non-linear interactions. This predictive ability contributes to the improvement of several objectives, including surface roughness, dross height, kerf width, kerf taper angle, and striation [123][124][125][126][127]. Researchers introduced a novel approach for predicting the quality of laser-cutting via the use of an artificial neural network.…”
Section: Ai Optimization Techniquesmentioning
confidence: 99%
“…9,19,20 Other cut quality characteristics, such as surface roughness, the width of HAZ and dross formation, were also used in optimization studies as primary objective criteria. 6,18,2125…”
Section: Introductionmentioning
confidence: 99%
“…9,19,20 Other cut quality characteristics, such as surface roughness, the width of HAZ and dross formation, were also used in optimization studies as primary objective criteria. 6,18,[21][22][23][24][25] From the literature review, it can be observed that the majority of laser cutting optimization research studies examined Nd:YAG laser cutting of aluminum alloys and stainless steel sheets of smaller thicknesses. Also, the majority of previous optimization studies considered simultaneous or separate optimization of two or more objective functions.…”
Section: Introductionmentioning
confidence: 99%